2013
DOI: 10.1111/1750-3841.12178
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Evaluation and Electronic Tongue for Sensing Flavored Mineral Water Taste Attributes

Abstract: In this article a trained sensory panel evaluated 6 flavored mineral water samples. The samples consisted of 3 different brands, each with 2 flavors (pear-lemon grass and josta berry). The applied sensory method was profile analysis. Our aim was to analyze the sensory profiles and to investigate the similarities between the sensitivity of the trained human panel and an electronic tongue device. Another objective was to demonstrate the possibilities for the prediction of sensory attributes from electronic tongu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Several literature sources concluded that electronic tongues are capable of predicting, for example Italian red wine taste attributes (BURATTI et al, 2007), apple juice preference (BLEIBAUM et al, 2002), or to discriminate between mineral waters (SIPOS et al, 2012). Moreover, electronic tongue has been moved further in trend of getting prediction models based on the results of consumers (BLEIBAUM et Acta Alimentaria 47, 2018 and experts (SIPOS et al, 2013) for predicting different sensory attributes of different food products.…”
mentioning
confidence: 99%
“…Several literature sources concluded that electronic tongues are capable of predicting, for example Italian red wine taste attributes (BURATTI et al, 2007), apple juice preference (BLEIBAUM et al, 2002), or to discriminate between mineral waters (SIPOS et al, 2012). Moreover, electronic tongue has been moved further in trend of getting prediction models based on the results of consumers (BLEIBAUM et Acta Alimentaria 47, 2018 and experts (SIPOS et al, 2013) for predicting different sensory attributes of different food products.…”
mentioning
confidence: 99%
“…According to the score, the electronic tongue can predict most of the relatively acceptable sensory attributes except bitterness [27]. Until now, most of the existing researches are based on the comparison of artificial sensory evaluation to determine the accuracy of the intelligent bionic instrument and the grades of food samples, so that the intelligent bionic instrument can accurately and digitally express the information of samples [28][29][30][31][32]. These studies are important for achieving high-precision biomimetic prediction of samples.…”
Section: Introductionmentioning
confidence: 99%
“…The bitterness of dairy protein hydrolysates was corresponded to the degree of hydrolysis which is analyzed by sizeexclusive and reverse-phase chromatography elution patterns [2]. Additionally, PLS regression has shown that attributes of flavored mineral water are correlated with an electronic tongue device [3]. Thus, PLS analyses have been successful in providing datasets of instrumental measurement for variables that explain the sensations in the mouth during eating.…”
Section: Introductionmentioning
confidence: 99%